2022
DOI: 10.1101/2022.10.27.514111
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Novel Role of Midbody-Associated mRNAs in Regulating Abscission

Abstract: Midbodies (MBs) have been shown to function during telophase as a recruiting hub, especially for ESCRT-III complex subunits, including CHMP4B, to regulate the abscission step of cytokinesis. However, the molecular machinery governing specific protein targeting and activation at the MB remains poorly understood. Until recently, it was thought that abscission regulating proteins, such as ESCRT-III complex subunits, accumulate at the MB by directly or indirectly binding to the MB resident protein, CEP55. However,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 52 publications
0
4
0
Order By: Relevance
“…As our lab recently discovered that the midbody and MBR are sites of active translation 52 , we sought to determine if common and commercial methods of isolating EVs also preserve translation capacity. Puromycin antibody labeling was used as a proxy for translation activity because the localization pattern is similar to HPG-Click-IT activity 52,88,89 . Here, cleared culture media was treated with puromycin for 10 minutes at 37°C.…”
Section: Ev Isolation Kits Reveal That Large Evs Have the Capacity To...mentioning
confidence: 99%
“…As our lab recently discovered that the midbody and MBR are sites of active translation 52 , we sought to determine if common and commercial methods of isolating EVs also preserve translation capacity. Puromycin antibody labeling was used as a proxy for translation activity because the localization pattern is similar to HPG-Click-IT activity 52,88,89 . Here, cleared culture media was treated with puromycin for 10 minutes at 37°C.…”
Section: Ev Isolation Kits Reveal That Large Evs Have the Capacity To...mentioning
confidence: 99%
“…Alternatively, Pav may be organizing actin within NE buds to organize the megaRNPs within. Additionally, a recent study showed that MKLP1 (mammalian Pav ortholog) accumulates at the midbody (a transient structure during cytokinesis [ 84,85 ] where it regulates RNA localization and spatio‐temporal translation. Interestingly, the midbody contains RNPs and are a site of active translation.…”
Section: Physical Aspects Of Ne Buddingmentioning
confidence: 99%
“…Studies on MB functions have extended beyond regulatory functions of cytokinesis, and now indicate their signaling capabilities 9 and ribonucleoprotein (RNP) properties 13,[32][33][34][35] . An array of proteins involved in translation, translational regulation, and RNA molecules are enriched in mitotic MBs 33,34,36 .…”
Section: Meiotic Midbodies Are Enriched In Ribonucleoproteinsmentioning
confidence: 99%
“…Recent work attributes this ability to the RNAs that are potentially translated or used as templates to inhibit gene function after MBRs are internalized 12 . In somatic cells, MBs and MBRs are enriched with translational machinery and speci c transcripts that are recruited via their 3' untranslated region sequence, providing further explanation of how MBRs could act as signaling organelles 12,13 . Because oocytes must produce proteins critical for successful meiosis and early embryogenesis, we hypothesized that MBs would locally translate proteins.…”
Section: Introductionmentioning
confidence: 99%